Te-Modulated Fe Single Atom with Synergistic Bidirectional Catalysis for High-Rate and Long–Cycling Lithium-Sulfur Battery - Guo, Jian; Chen, Lu; Wang, Lijun; Liu, Kangfei; He, Ting; Yu, Jia; Zhao, Hongbin (Nano-Micro Letters, 2025)
Single-atom catalysts (SACs) have garnered significant attention in lithium-sulfur (Li-S) batteries for their potential to mitigate the severe polysulfide shuttle effect and sluggish redox kinetics. However, the development of highly efficient SACs and a comprehensive understanding of their structure–activity relationships remain enormously challenging. Herein, a novel kind of Fe-based SAC featuring an asymmetric FeN5-TeN4 coordination structure was precisely designed by introducing Te atom adjacent to the Fe active center to enhance the catalytic activity. Theoretical calculations reveal that the neighboring Te atom modulates the local coordination environment of the central Fe site, elevating the d-band center closer to the Fermi level and strengthening the d-p orbital hybridization between the catalyst and sulfur species, thereby immobilizing polysulfides and improving the bidirectional catalysis of Li-S redox. Consequently, the Fe-Te atom pair catalyst endows Li-S batteries with exceptional rate performance, achieving a high specific capacity of 735 mAh g−1 at 5 C, and remarkable cycling stability with a low decay rate of 0.038% per cycle over 1000 cycles at 1 C. This work provides fundamental insights into the electronic structure modulation of SACs and establishes a clear correlation between precisely engineered atomic configurations and their enhanced catalytic performance in Li-S electrochemistry. Highlights: 1 The Te modulator induces a polarized charge distribution to optimize the electronic structure of the central Fe site, elevating the d-band center and enhancing the density of states near the Fermi level. 2 Strengthened d-p orbital hybridization between the catalyst and sulfur species optimizes the adsorption behavior toward LiPSs and facilitates the bidirectional redox process of Li-S batteries. 3 The Fe-Te atom pair catalyst endows Li-S batteries remarkable rate performance, extraordinary cycling stability and anticipated areal capacity.